2016
DOI: 10.3892/ol.2016.4401
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and corresponding factors: A novel perspective on the risk factors of esophageal cancer

Abstract: Abstract. Esophageal cancer is the eighth most common type of cancer in the world, and the sixth most common cause of mortality from cancer. Alcohol consumption is the major risk factor for esophageal cancer, due to the worldwide prevalence and high carcinogenicity of the ethanol metabolite. In epidemiological studies, the efficiency of alcohol intake to enhance the risk of esophageal cancer is altered by daily ethanol consumption, type of alcoholic beverages ingested, time since quitting drinking, age of drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 125 publications
0
25
0
3
Order By: Relevance
“…People with a mutated ALDH2-2 allele accumulate acetaldehyde and, if they ingest alcohol, they are exposed to a much higher risk of alcohol-mediated cancers than people with a wildtype allele. ALDH2-2 mutations occur commonly in (East) Asian countries [5,17]. In Japan for example, up to 40% of the population are heterogenous for the ALDH2 gene and are therefore at a higher risk of alcohol-related upper digestive tract cancers [18].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…People with a mutated ALDH2-2 allele accumulate acetaldehyde and, if they ingest alcohol, they are exposed to a much higher risk of alcohol-mediated cancers than people with a wildtype allele. ALDH2-2 mutations occur commonly in (East) Asian countries [5,17]. In Japan for example, up to 40% of the population are heterogenous for the ALDH2 gene and are therefore at a higher risk of alcohol-related upper digestive tract cancers [18].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…The list of alcohol-associated cancers is still growing. Even modest use of alcohol may increase cancer risk, in particular when combined with either tobacco smoking or excess body weight [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Because excess alcohol consumption poses a significant global public health issue, there have been efforts to minimize exposure to alcohol, which has important implications for ESCC prevention and alcohol abuse. 2,3 However, variation in alcohol consumption alone does not explain the differing incidence between regions at high and low risk of ESCC. Other etiological factors associated with ESCC should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…There is no final consensus on the list of risk factors for oesophageal cancer, but in many studies smoking and alcohol drinking showed a strong association with squamous cell carcinoma [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%